Influence of vertical trailing on seed yield and quality during seed production of bottlegourd (Legenaria siceraria) cv. Pusa hybrid-3 - KALYANRAO; B. S. TOMAR; BALRAJ SINGH (Seed Research, 2026)
The present experiment was carried out at Seed Production Unit, IARI, New Delhi, during kharif 2009-10 and 2010-11 with two growing systems viz. trailing and traditional method, whereas laboratory tests were conducted at Division of Seed Science and Technology, IARI New Delhi. The seed and pollen parent were grown following block method in 3:1 ratio. Significantly higher vine length and number of nodes per vine at flowering period was recorded in trailing as compared to traditional method. The number of fruit set (6.65) and matured fruit per vine (5.30) were significantly higher in trailing than those of traditional method. The fruit development attributes i.e. fruit weight, fruit length and fruit width was also significantly higher in trailing as compared to traditional method. The comparative results of seed yield attributes showed that the number of filled seeds/fruit (584.7), seed yield/vine (517.5 g) and seed yield/acre (689.6 kg) were significantly higher in trailing. The seed quality attributes viz. germination percentage, seedling length, seedling dry weight, vigour index I & II and seed moisture content, immediately after harvest were also significantly superior in trailing method. The cost-benefit analysis of hybrid seed production showed higher BC ratio in trailing (3.87) than those in traditional method (2.10).